ANALISA BAKTERI Escherichia coli DAN Salmonella sp PADA TELUR AYAM KAMPUNG - Della Ika Putri Damayanti; Mutiarawati Diah Titik; Suliati Suliati (Analis Kesehatan Sains, 2021)
Meanings of animal origin are often contaminate by microorganism, one of it is chicken eggs. Free range chicken is often consumed raw for medicinal purposes without knowing any contamination in it. Free range chicken are often associated with the genesis of foodborne diseases that can cause ailments in the form of diarrheal and gastroenteristic diseases. According to data provided by the 2018 ministry of health, there are approximately 7 million cases of diarrheal disease every year. The bacteria responsible for diarrhea is Salmonella sp, Escherichia coli and Staphylococcus aureus. This type of research is laboratory experimental research through culture. The population of this study was eggs obtained from the village of Tanggul Kulon RT 01/RW 07 Jember. The sample of this research is free range chicken taken by purposive sampling based on criteria. The place of this research was conducted at the Bacteriology Laboratory of Poltekkes Surabaya from January to April 2021. The result showed 4 out of 12 positive samples identified as Escherichia coli and 8 out of 12 positive samples identified as Salmonella parathypi A bacteria